Variation in the Electromagnetic Radiation Exposure Level from Cellular Mobile Base Station Antennas to its Vicinity- A Study - Tewary, Jyotirmay; Dey, Pratik; Das, Amitesh; Roy, Kousik; Kumar Parui, Susanta (International Journal of Computer Sciences and Engineering, 2025)
Men made atmospheric exposure of Electromagnetic radiations (EMR) are now increasing almost exponentially in the last few decades. With rapid development in the field of communication, the mobile base station antenna and its associated health hazards are now led to growth of public concern for human exposure to Electromagnetic field (EMF) and its various health effects. The Electromagnetic Pollution (EMP) levels are now reaching alarming proportion for the whole biological system. The present study were aim to investigate the variation in the electromagnetic radiation exposure level from mobile base station antenna to its vicinity in terms of power density and electric field. Measurement was carried out with the help of three axis electromagnetic field strength meter. Three different cases were considered. The EM radiation exposure level from mobile Base Transceiver Station (BTS) was measured at a distance of 10m, 15m and 20m for the first, second and third cases respectively at different co-ordinate positions. Results are tabulated in terms of Power Density (PD) and Electric field. It has been observed that the electromagnetic radiation exposure level from mobile BTS varies with distance from BTS tower at different co-ordinate position. However the measured values of Power Density and electric field were well below the maximum permissible exposure level set by the International Commission on Non-ionizing Radiation Protection (ICNIRP) authority. The outcome of our study reveals that the EM radiation exposure level from BTS varies with distance and reached to its optimum value at a particular region (most sensitive zone) thereafter again the radiation level decrease gradually with distance from BTS at different co-ordinate positions.